IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA SEKRETARIAT DPRD KOTA BANJAR - Riyan Anggara (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2023)
Implementation of the principles of good corporate governance at the Banjar City Council Secretariat. Agencies are required to be more effective and efficient in their work, in order to be able to provide maximum service to the public. So we need a concept of good governance (Good Corporate Governance) for the sustainability of institutions in the long term. Based on this background, the formulation of the problem is how to implement the principles of good corporate governance at the DPRD secretariat of Banjar City. The research method used in this study is a research method using a qualitative approach. The research location is in the Banjar City DPRD Secretariat office. Data collection techniques used by researchers are interviews, observation, and documentation. The data analysis technique used is the data analysis technique from Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. This study describes the implementation of the principles of good corporate governance at the DPRD secretariat of Banjar City. The implementation of Good Corporate Governance is based on five principles, namely: transparency, accountability, responsibility, independence, fairness and fairness. Keywords: Implementation; good corporate governance; Banjar City Government